Macrochaete gen. nov. (Nostocales, Cyanobacteria), a taxon morphologically and molecularly distinct from Calothrix - Berrendero Gómez, Esther; Johansen, Jeffrey R; Kaštovský, Jan; Bohunická, Markéta; Čapková, Kateřina (Journal of phycology, 2016)
Historically, the genus Calothrix included all noncolonial, tapered, heterocytous filaments within the cyanobacteria. However, recent molecular phylogenies show that "Calothrix" defined in this sense represents five distinct clades. The type species of Calothrix is marine, with solitary basal heterocytes, no akinetes, and distal ends tapering abruptly into short hairs. We examined the morphology and phylogeny of 45 tapering cyanobacteria in the Rivulariaceae, including freshwater and marine representatives of both Calothrix (35 strains) and its sister taxon Rivularia (10 strains). The marine Calothrix fall into two lineages, but we lack the generitype and so cannot identify the clade corresponding to the type species. The freshwater and soil Calothrix fall into the C. parietina clade and are characterized by having a basal heterocyte, no akinetes, and gradual tapering-but not into a long hyaline hair. Macrochaete gen. nov. is a freshwater taxon sister to the Calothrix lineages but clearly separated from Rivularia. The species in this genus differ morphologically from Calothrix by their ability to produce two heteromorphic basal heterocytes and specific secondary structures of the 16S-23S ITS. An additional feature present in most species is the presence of a distal, long hyaline hair, but this character has incomplete penetrance due to its expression only under specific environmental conditions (low phosphate), and in one species appears to be lost. We recognize three species: M. psychrophila (type species) from cold environments (high mountains, Antarctica), M. santannae from wet walls of subtropical South America, and M. lichenoides, a phycobiont of lichens from Europe.
Keywords: půdní mikrobiologie; Cyanobacteria; Macrochaete; Fresh Water; Phylogeny; DNA, Bacterial; Seawater; Rivulariaceae; mořská voda; sinice; Calothrix; fylogeneze; 16S rRNA gene; sladká voda; 16S-23S ITS region; polyphasic approach; DNA bakterií; Soil Microbiology